ECB monetary expansions and euro area TARGET2 imbalances: a balance-of-payment-based decomposition - Marcello Minenna; Giovanni Dosi; Andrea Roventini (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
The recent financial literature seems to have reached a consensus about the influence of European Central Bank (ECB) unconventional monetary policies in explaining the multiple divergent trends of TARGET2 (T2) balances in the eurozone from 2010 and the ensuing segregation of risks in each national economy. According to the ECB, 'mechanical' effects in the accounting of government bonds explain the explosion of T2 balances. Divergence could therefore not be attributable to a 'capital flight' from peripheral economies towards northern Europe. Such an explanation does not seem to fit well with the analysed cases of Italy, Spain, and Germany. A decomposition of the T2 balances through the analysis of the financial accounts of the balance of payments shows indeed that the deterioration in the balances of Italy and Spain is mainly due to a shift of private-sector financial wealth from government securities to foreign assets (bonds, shares, and mutual funds). In the case of Germany, the abnormal growth of T2 balances is mainly attributed to the persistent influence of current-account surpluses reaching 6–8 percent of GDP and increasing due to the indirect effects of quantitative easing policies on the exchange rate between the euro and the other major international currencies.
Keywords: E42; E44; E52; E58; F32; F34; 330; capital flows; payment system; financial crisis; quantitative easing; interbank lending